Early Motor Repertoire in Infants With Biliary Atresia: A Nationwide Prospective Cohort Study. Issue 4 (April 2021) - Rodijk, Lyan H.; Bos, Arend F.; Verkade, Henkjan J.; de Kleine, Ruben H.; Hulscher, Jan B.F.; Bruggink, Janneke L.M.
ABSTRACT: Objectives: The aim of the study was to assess the neurological status in infants with biliary atresia (BA) at time of diagnosis, using Prechtl's validated General Movement Assessment. Methods: Infants diagnosed with BA were prospectively included in a nationwide cohort study. From birth to approximately 46 weeks of postmenstrual age (PMA), general movements (GMs) are defined as "writhing movements." At 46 to 49 weeks PMA, "'fidgety movements" emerge. The infant's early motor repertoire was recorded on video before Kasai portoenterostomy. We scored GM optimality scores (min–max 5–42) or motor optimality scores (MOS, min–max 5–28) as appropriate. We defined GM optimality scores <36 and MOS <26 as atypical, and compared the results with 2 reference groups of healthy peers. Results: We assessed GMs in 35 infants with BA (11/35 boys, gestational age 40 weeks [36–42], birth weight 3370 g [2015–4285]). At time of diagnosis (PMA 47 weeks [42–60]), 16 infants (46%) showed atypical GMs. The proportion of infants with atypical GMs was significantly higher in BA (46%) than in 2 reference groups of healthy infants (vs 10%, P < 0.001; vs 18%, P  < 0.001). Total and direct bilirubin levels were 165 μmol/L (87–364) and 134 μmol/L (72–334), respectively, height z score was 0.05 (–2.90, 1.75), weight z score −0.52 ([−2.50, −0.20) and mean upper arm circumference z score −1.80 (−2.50, −0.20). We found no statistically significant relation between atypical GMs and clinical variables. Conclusions: Almost half of the infants with BA showed atypical GMs at time of diagnosis, suggesting neurological impairment. Close monitoring of these infants is warranted to determine their individual neurodevelopmental trajectories. Abstract : Supplemental Digital Content is available in the text